A review of health security and vaccine diplomacy during COVID-19 pandemic - Ravichandran Moorthy; Lakshmy Naidu (Intelektual Pustaka Media Utama, 2022)
The coronavirus disease 2019 (COVID-19) pandemic raises several public health concerns that impact various aspects of people's lives. The severity and spread of infection are extremely rapid, spreading out of control globally. Aside from illness and death, it presents a slew of long-term health concerns among the population. Therefore, the pandemic has manifested into a major health security issue, impacting the population globally. Health securitization refers to recognizing the presence of an existential health threat, and authorities can devote resources to manage the risks. Although vaccinations are required for long-term management of this disease, the vaccination procedure is often plagued by access, efficacy, and vaccine prioritization issues. By employing an interpretative social science approach, the article argues that the COVID-19 pandemic needs to be securitized at the state and international levels, and vaccines as public-good should be accessible to everyone without discrimination or prioritization and diplomatic interests. The study found, firstly, that many countries have adopted health securitization and coordinated efforts by international agencies. Secondly, vaccine hoarding by richer countries has created a disparity in the rate and coverage of vaccination in other regions. Thirdly, vaccine donation by richer countries is only a temporary solution. A robust vaccine allocation mechanism is needed for more comprehensive and equitable vaccination coverage.